2014
DOI: 10.1080/13548506.2014.986139
|View full text |Cite
|
Sign up to set email alerts
|

Evident or doubtful? How lexical hints in written information influence laypersons’ understanding of influenza

Abstract: There are clear differences in the way written information on health issues presents research findings. In some cases, the source of a piece of information (e.g. "expert professor") is highlighted to emphasize its credibility and relevance. In other cases, the impact of a certain argument is stressed by avoiding hints on tentativeness such as "mostly" or "up to now." This article examines whether and how far such differences influence laypersons' comprehension of the contents provided. In an experimental setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…For instance, the use of lexical markers of tentativeness (lexical hedges as “possibly” or “seem to”) in texts lead to arguments being evaluated as weaker and sources or persons being perceived as less trustworthy and competent (Blankenship & Holtgraves, 2005; Burrel & Koper, 1998; Hosman & Siltanen, 2011). However, the presence of such lexical hedges also leads readers to focus more on the actual information in the text (Mayweg-Paus & Jucks, 2014).…”
Section: Taking Two-sided Perspectives In Discussion As An Indicator mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the use of lexical markers of tentativeness (lexical hedges as “possibly” or “seem to”) in texts lead to arguments being evaluated as weaker and sources or persons being perceived as less trustworthy and competent (Blankenship & Holtgraves, 2005; Burrel & Koper, 1998; Hosman & Siltanen, 2011). However, the presence of such lexical hedges also leads readers to focus more on the actual information in the text (Mayweg-Paus & Jucks, 2014).…”
Section: Taking Two-sided Perspectives In Discussion As An Indicator mentioning
confidence: 99%
“…An argument was defined as a statement giving information on the topic and thereby including either pro or contra evidence as well as an indication of whether there was proof for this evidence (e.g., “In one of their studies, Prof. Rickert and colleagues found that poor school performance and the frequent use of specific computer games are interrelated—even in children from moderately or highly educated families that provide optimal preconditions for success at school”). We ensured that the number of other potentially influencing factors, that is, references to a source and linguistic markers of tentativeness (Mayweg-Paus & Jucks, 2014; Thiebach et al, 2015), was balanced between the pro and contra arguments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors influence information seekers’ credibility and trustworthiness judgments [15-17], but the language style of an information source seems to be an especially influential factor [18-22]. Thon and Jucks [18], for example, showed that the authors of health information forum posts were rated as more trustworthy and their information as more credible when they used an everyday language style (eg, “heart attack”) instead of a technical language style (eg, “myocardial infarction”).…”
Section: Introductionmentioning
confidence: 99%
“…Thon and Jucks [18], for example, showed that the authors of health information forum posts were rated as more trustworthy and their information as more credible when they used an everyday language style (eg, “heart attack”) instead of a technical language style (eg, “myocardial infarction”). Furthermore, Mayweg-Paus and Jucks [22] showed that participants accepted information from an online health article to a higher degree and processed it in more depth when the article was written in a tentative language style (eg, “is presumably similar”) rather than a nontentative language style (eg, “is similar”). Tentativeness, however, does not just infuence trustworthiness and credibility judgments.…”
Section: Introductionmentioning
confidence: 99%